THE REPATRIATION OF CULTURAL ASSETS FROM FOREIGN MUSEUM COLLECTIONS: A HISTORICAL-THEORETICAL AND DISCURSIVE ANALYSIS (Journal of history, 2026)
This article examines the place of historical and cultural artefacts acquired during the imperial period in contemporary scholarly discourse, alongside the historiographical evolution of the repatriation issue. The aim of the study is to analyse the development of theoretical perspectives and practical experiences in returning cultural property, the role of international legal instruments and museum policies, as well as modern approaches to ensuring access to cultural heritage. The methodology combines historiographical review, comparative-historical method, content analysis, systemic-structural approach, and bibliographic analysis.The novelty of this research lies in its comprehensive consideration of access to cultural heritage not only within the framework of repatriation but also through forms of international cooperation that hold cultural, ethical, and symbolic significance. The paper analyses the role of the 1970 UNESCO Convention and the 1995 UNIDROIT Convention, the impact of postcolonial critique, the transformation of the “universal museum” concept, and contemporary museum practices in provenance research.In addition, the study analyses the works of Soviet and domestic scholars (I. Neustupny, I. Benes, V. Gluzinsky, V. Gritskevich, P. van Mensch), which reveal the theoretical and methodological development of museology and its relevance in contemporary scholarly discourse.The findings indicate that in recent decades, museums worldwide have strengthened partnerships with former colonial countries by implementing joint exhibitions, long-term loans, digital repatriation, and multi-voice curatorial projects, thus fostering connections based on cultural equality and mutual understanding. This experience is also relevant for Kazakhstan, as it offers pathways to resolve the return of Kazakh ethnographic heritage from foreign museums through mutually beneficial, conflict-free solutions.
Keywords: historical and cultural values, repatriation, historiography, museum transformation, international cooperation.